СОСТОЯНИЕ КЛЕТОЧНЫХ МЕМБРАН ЭРИТРОЦИТОВ КРОВИ КРЫС-РЕЦИПИЕНТОВ ЧЕРЕЗ3, 6 и9 МЕСЯЦЕВ ПОСЛЕ ВВЕДЕНИЯ АЛЛОГЕННЫХ МОНОНУКЛЕАРОВ (Experimental biology, 2015)
The intravenous injection of allogenic mononuclear cells (MNCs) to recipient rats resulted in a decrease of erythrocyte membranes’ osmotic resistance in a hypotonic NACI solution, in hypertonic (0.4 M) sucrose solution, and at hyperosmotic shock and effect of the temperature factor during 3-6 months after transplantation. The restoration of red blood cells hemolysis to the control level was observed 9 months after MNCs transplantation.
Keywords: allogenic mononuclear cells; transplantation